Sosialisasi peningkatan keuangan literasi digital bagi istri Purnawirawan POLRI Megamendung Bogor (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Advances in financial technology require people to have adequate digital financial literacy in order to be able to use financial services safely and wisely. However, there are still many community groups that face limited understanding, including the wife of a retired National Police officer in Megamendung, Bogor. This Community Service Program (PKM) is designed to increase their knowledge, awareness, and skills in managing finances through digital services. The implementation method includes socialization, counseling, interactive discussions, and practical guidance in the use of digital financial applications such as e-wallets and online banking services. Evaluation of activities was carried out through observation, question and answer sessions, and measurement of the level of understanding before and after socialization. The results showed a significant increase in participants' understanding of the concept of digital financial literacy, including benefits and risks to watch out for, such as digital fraud and irregular financial management. In addition, participants also experienced an increase in confidence in using digital financial services for daily needs. This program is expected to encourage family financial independence and improve the economic welfare of the wives of retired POLRI officers in Megamendung, Bogor, as well as become a model for community empowerment in facing the challenges of the digital era.